Digital Transformation of Culture - Khakimov, Erkin (International Journal of Formal Education, 2024)
The article examines the problem of cultural transformation under the influence of digitalization, its main directions and prospects, its positive and negative consequences and impact on the main subsystems of the human psyche and possible methods of prevention.